IMPACT OF SELECTED METEOROLOGICAL PHENOMENA ON FLIGHT OPERATIONS - Krollova, Sandra (Doprava a spoje, 2012)
The paper provides a complex view on selected weather phenomena that significantly affect flight operation. The discussed weather hazards are of various time and spatial scale, with different effects on aircraft during the flight phases. In several topics some statistical data supplement the theoretical backgroung and confirm the importance and relevance of knowledge of aviation weather hazards.